2004
DOI: 10.1159/000079130
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Changes in Blood Pressure and Frequency of Related Complications in Elderly Israeli Patients with Essential Hypertension

Abstract: Background: Earlier studies on hypertension demonstrated seasonal variations in different age groups. However, slightly greater fluctuations were found in the hypertensive elderly. Objective: We conducted a prospective 5-year study from January 1997 to December 2001 to evaluate the seasonal variation in blood pressure and the variables of age, gender, body mass index and related complications in elderly Israeli patients with essential hypertension. Methods: Blood pressure was measured in four seasons in 182 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
38
3
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 15 publications
4
38
3
2
Order By: Relevance
“…Previous report [6] had shown greater seasonal BP fluctuations among elderly patients with HTN whose mean SBPs and DBPs were higher during the winter compared to the summer.…”
Section: Introductionmentioning
confidence: 67%
See 3 more Smart Citations
“…Previous report [6] had shown greater seasonal BP fluctuations among elderly patients with HTN whose mean SBPs and DBPs were higher during the winter compared to the summer.…”
Section: Introductionmentioning
confidence: 67%
“…Theories on climate changes and their impact on organisms originated in the period of Enlightenmentbut continuous recordings of weather conditions and their relationship with life parameters was not possible until the development of physics and technology, specifically, the invention of the thermometer and barometer, AP is the most objective meteorological factor that has the same influence on humans both indoors and outdoors. Several studies have confirmed that the flow of specific air masses is correlated with changes in wellbeing and the accompanying changes in BP [2][3][4][5][8][9][10], and that patients with chronic diseases are reportedly more liable to be affected by weather changes compared to healthy individuals [6]. In patients with hypertension (HTN), even small fluctuations in BP influenced by weather can potentially result in serious neurological and cardiovascular complications.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…5-10 mm Hg) have long been known, both in normotensive and hypertensive subjects. Nevertheless, perhaps because adverse cardiovascular events are more frequent in winter, it is the practice in some quarters to decrease antihypertensive medication in summer, and/or increase in winter (Charach, Rabinovich & Weintraub, 2004). However, this is controversial.…”
Section: Introductionmentioning
confidence: 99%